Wastewater and sludge valorisation: a novel approach for treatment and resource recovery to achieve circular economy concept - Kathi, Srujana; Singh, Siril; Yadav, Rajni; Singh, Anand Narain; Mahmoud, Alaa El Din (Frontiers in Chemical Engineering, 2023)
Global demand for freshwater is rapidly escalating. It is highly essential to keep pace with the necessities of the increasing population. The effluents of wastewater are gradually identified as a reservoir of resources for energy generation and economic boom. Henceforth, most wastewater and sludge have great potential for reuse and recycling. The re-utilization and valorization of wastewater and sludge contribute to accomplishing sustainable development goals, combating water scarcity, and alleviating adverse environmental impacts of wastewater on the environmental components. The present article highlights the most novel approaches for wastewater treatment for the waste valorization of different industrial origins and the generation of value-added products and recovery of biopolymers, vitamins, enzymes, dyes, pigments, and phenolic compounds. In addition, we have addressed a critical overview of the barriers to the large-scale application of resource recovery strategies and economic, environmental, and social concerns associated with using waste-derived products.